Znaczenie współpracy międzysektorowej dla kształtowania atrakcyjności obszaru turystycznego - Rapacz, Andrzej (International cooperation significance in shaping customer appeal of a tourist region, 2005)
Public-private partnership as the form of inter-sector cooperation becomes more and more popular in Poland. Lack of legislation in this field (applicable Act) does not pose any barrier for the development of public and private sector cooperation in tourist regions. They take up activities directed towards the development of semi and tourism infrastructure in these regions, broadening an offer and improving customer appeal of the area, as well as its competitive advantage. The study points to forms and stages of constructing public-private partnership in tourist resorts and regions. There are also presented examples of activities which illustrate the development of inter-sector cooperation in tourism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 96-106